Empowering individual learners: Call for promoting inclusivity among medical students with different learning styles - Saurabh RamBihariLal Shrivastava; Novina Aryanti; Arief Wibawa (Wolters Kluwer Medknow Publications, 2023)
In the field of delivery of medical education, it is crucial that teachers acknowledge that every medical student possesses a unique learning style to acquire knowledge. There is an immense need to recognize and identify individual learning styles of medical students, and this is because of multiple reasons. Once we are aware of the importance and scope of learning styles in learning and career progression, it is the need of the hour that we must ensure inclusivity (accommodate and address the learning needs of students with varied learning styles). In conclusion, there is an immense need to be aware of the learning styles of medical students to facilitate the effective delivery of medical education. However, considering the variability in learning styles and their importance in facilitating the acquisition of knowledge and skills, it is crucial to promote an inclusive learning environment in each medical college.